2020
DOI: 10.1002/1878-0261.12818
|View full text |Cite
|
Sign up to set email alerts
|

The FABP12/PPARγ pathway promotes metastatic transformation by inducing epithelial‐to‐mesenchymal transition and lipid‐derived energy production in prostate cancer cells

Abstract: Early stage localized prostate cancer (PCa) has an excellent prognosis; however, patient survival drops dramatically when PCa metastasizes. The molecular mechanisms underlying PCa metastasis are complex and remain unclear. Here, we examine the role of a new member of the fatty acid-binding protein (FABP) family, FABP12, in PCa progression. FABP12 is preferentially amplified and/or overexpressed in metastatic compared to primary tumors from both PCa patients and xenograft animal models. We show that FABP12 conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 78 publications
(115 reference statements)
0
30
0
Order By: Relevance
“…A separate study from this one has also shown independence of FABP5 expression from PCa clinical outcomes [49]. reported to be highly expressed in PCa [51], and we have studied and proposed a role for FABP12 in promoting PCa metastasis and progression (discussed below) [29]. Human PCa disease-free (DF) patient survival analysis based on mRNA levels of each FABP located at 8q21.13.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…A separate study from this one has also shown independence of FABP5 expression from PCa clinical outcomes [49]. reported to be highly expressed in PCa [51], and we have studied and proposed a role for FABP12 in promoting PCa metastasis and progression (discussed below) [29]. Human PCa disease-free (DF) patient survival analysis based on mRNA levels of each FABP located at 8q21.13.…”
Section: Introductionmentioning
confidence: 94%
“…These promising results, combined with the documented roles of FABPs in cancer progression, support further development of FABP-targeted inhibitors and therapies for the treatment of PCa. acid synthesis, lipolysis and angiogenesis pathways [48,76,93,139], whereas FABP12 induces EMT and oxidative phosphorylation [29]. PPARs are important mediators of FABP functions presumably through fatty acid transfer from FABPs to PPARs, although the details remain elusive.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations